GUIDANCE AND COUNSELING (BK) TEACHER COMMUNICATION PATTERNS WITH STUDENT VICTIMS OF BULLYING - Nua, Salma P; Kede, Adrian; Syaiful, Muh (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2023)
A communication pattern is a form or design of a relationship between two or more people sending and receiving messages related to the two components. Communication strategies are carried out by making the right design to change people's behavior. This study aimed to determine the communication pattern of BK teachers with students who were victims of Bullying at SMA Negeri 1 Kabila. This research was conducted at SMA Negeri 1 Kabila. The method used in the study is the qualitative research method. The data analysis methodology uses Miles and Huberman's data analysis methodology, which consists of the data collection stage, data reduction, data presentation, and conclusion/evaluation drawing stage. As a result, it was found that the communication pattern between BK teachers and students who were victims of Bullying was a one-way communication pattern where only BK teachers and BK teachers spoke. Students actively communicate their messages. A two-way communication pattern that involves the BK teacher as a listener, notes, and responses from students and many stakeholders: BK teachers, class teachers, parents, and student friends Involves multi-way communication patterns and interactions in the communication process.Â